Development of an indirect ELISA to detect Corynebacterium pseudotuberculosis specific antibodies in sheep employing T1 strain culture supernatant as antigen - Rebouças,Miriam F. (2013)
Corynebacterium pseudotuberculosis is the etiologic agent of caseous lymphadenitis (CLA), a chronic disease that affects goats and sheep, characterized by granuloma formation in subcutaneous and internal lymph nodes. CLA causes significant economic losses to commercial goat herds. In this study, we aimed to test secreted antigens secreted from T1 strain bacteria grown in brain heart infusion (BHI) broth in an indirect ELISA system to determine the presence of specific immunoglobulins against C. pseudotuberculosis. We analyzed the BHI antigen electrophoretic profile and the recognition pattern by infected sheep sera samples. The ELISA results were compared with multiplex PCR assay and IFN-gamma production. The ELISA was able to discriminate between negative and positive animals, with a sensitivity of 89% and a specificity of 99%, using microbiological isolation as gold standard. When this assay was compared with multiplex PCR and specific IFN-gamma quantification, six discrepant results were found among thirty-two samples. We concluded that the ELISA using antigens secreted from C. pseudotuberculosis T1 strain growth in BHI broth culture can be used for the serodiagnosis of CLA in sheep.